Compromised Behavior and Gamma Power During Working Memory in Cognitively Healthy Individuals With Abnormal CSF Amyloid/Tau - Rochart, Roger; Liu, Quanying; Fonteh, Alfred N.; Harrington, Michael G.; Arakaki, Xianghong (Frontiers in Aging Neuroscience, 2020)
Abstract Research shows that gamma activity changes in Alzheimer’s disease (AD), revealing synaptic pathology and potential therapeutic applications. We aim to explore whether cognitive challenge combined with quantitative EEG (qEEG) can unmask abnormal gamma frequency power in healthy individuals at high risk of developing AD. We analyzed low (30-50 Hz) and high gamma (50-80 Hz) power over six brain regions at EEG sensor level (frontal/central/parietal/left temporal/right temporal/occipital) in a dataset collected from an aging cohort during N-back working memory (WM) testing at two different load conditions (N = 0 or 2). Cognitively healthy (CH) study participants (> 60 years old) of both sexes were divided into two subgroups: normal amyloid/tau ratios (CH-NAT, n=10) or pathological amyloid/tau (CH-PAT, n=14) in cerebrospinal fluid (CSF). During low load (0-back) challenge, low gamma is higher in CH-PATs than CH-NATs over frontal and central regions (p=0.014~0.032, effect size (Cohen’s d) = 0.95~1.11). However, during high load (2-back) challenge, low gamma is lower in CH-PATs compared to CH-NATs over the left temporal region (p=0.045, Cohen’s d = -0.96), and high gamma is lower over the parietal region (p=0.035, Cohen’s d = -1.02). Overall, our studies show a medium to large negative effect size across the scalp (Cohen’s d = -0.51~ -1.02). In addition, low gamma during 2-back is positively correlated with 0-back accuracy over all regions except the occipital region only in CH-NATs (r=0.69~0.77, p=0.0098~0.027); high gamma during 2-back correlated positively with 0-back accuracy over all regions in CH-NATs (r=0.68~0.78, p=0.007~0.030); high gamma during 2-back negatively correlated with 0-back response time over parietal, right temporal, and occipital regions in CH-NATs (r=-0.70~-0.66, p=0.025~0.037). We interpret these preliminary results to show: 1) gamma power is compromised in AD-biomarker positive individuals, who are otherwise cognitively healthy (CH-PATs); 2) gamma is associated with WM performance in normal aging (CH-NATs) (most significantly in the frontoparietal region). Our pilot findings encourage further investigations in combining cognitive challenges and qEEG in developing neurophysiology-based markers for identifying individuals in the prodromal stage, to help improving our understanding of AD pathophysiology and the contributions of low- and high-frequency gamma oscillations in cognitive functions.